Art as a Catalyst. Issue 1 (22nd October 2020) - Bubla, Eva
The socio-ecological challenges of recent times questioned the roles and responsibilities of artists and cultural practitioners. Several artists approached current issues by imagining new ways of living for a more sustainable form of future, attempting to trigger social transformation, a shift in values, changes in environmental issues, or a crucial system change. Is art truly capable of making a difference? The case studies examine the work of individual artists, artist collectives and cross-sectoral collaborations operating in Indonesia, India and Hungary, and through their work explore the potential of art as a catalyst.